STRATEGI PENANGANAN KEMISKINAN DI KABUPATEN BOGOR - Ade Triono; Djunita Warsita (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2019)
Strategy for Poverty Management in Bogor Regency. This study aims to describe the strategy of handling poverty in Bogor Regency carried out by both the Regional Government and the Central Government. The method used in this study is descriptive analytical. Data is collected through observation, interviews, documentation studies and literature relating to these handling efforts. Operationalization of data collection is described in concepts, variables, dimensions, and indicators. The data is analyzed using SWOT Analiisis, to find out the strengths, weaknesses, opportunities and threat, so that the problem can be mapped to overcome them. The results show that the efforts of the Bogor District Government to overcome the obstacles to the problem of poverty are carried out in the form of the involvement of local governments in empowering the community economy, by implementing poverty reduction policies and programs from both the local government and the central government. Keywords: strategy, policy, handling, poverty, Bogor.